Optical properties and thermal stability of Gd1-xNdxBaCo2O5+δ ceramics for high temperature air-stable solar thermal conversion. (15th January 2023) - Gao, Yalin; Zhou, Hong; Yin, Jialiang; Fang, Zhenggang; Liu, Heng; Liu, Jun; Lu, Chunhua; Xu, Zhongzi
Highlights: The photothermal conversion performance of Gd0.7 Nd0.3 BaCo2 O5+δ was better than that of Silicon Carbide which was commercial solar thermal conversion material. Gd0.7 Nd0.3 BaCo2 O5+δ had low infrared radiation heat loss at high temperature. Gd0.7 Nd0.3 BaCo2 O5+δ exhibited excellent thermal stability at 800 ℃ in air. Abstract: The efficiency of the concentrated solar power (CSP) framework is significantly influenced by the operating temperature. The solar thermal conversion material with high efficiency and good stability at high temperature in air environment is of importance to obtain the high operating temperature. Here, the optical properties and thermal stability of Gd1-x Ndx BaCo2 O5+δ (0 ≤ x ≤ 0.4, GNBCOx) ceramics were studied to assess their possibility to be applied as high temperature solar absorbers. Results presented that GNBCOx exhibited high absorptance in the solar spectrum and minimal radiation heat loss at infrared wavelengths. In addition, the GNBCOx ceramics demonstrated excellent stability at 800 ℃ in air, indicating that the GNBCOx ceramics could be applied as solar thermal conversion material for upcoming concentrated solar power systems.